Coeliac disease – what do dental health personnel know? - Storvolleng, Erlend Mikal Trolie; Blix Christensen, Lene (UiT Norges arktiske universitet, 2019)
Introduction: This master thesis investigates the knowledge which dental health personnel possesses regarding the correlation between coeliac disease and oral health, and the factors that may influence this knowledge. Material and methods: A questionnaire have been sent out to all dentists and dental hygienists employed in the public dental service in Nordland and Troms. One hundred and forty-three answered the questionnaire, giving a response rate of 58 percent. The respondents were divided into three groups according to the result of the questionnaire, a “high score” group, a “middle score” group and a “low score” group. The “high score’’ and the “low score” groups, a total of 59 participants, were included in the final analysis. Results: Dental health personnel reported in this study that they do not have enough information regarding the correlation between coeliac disease and oral health. The results indicate that several information sources are beneficial for increased knowledge.